Agreement between clinicoradiological signs at diagnosis and radiohistological analysis after neoadjuvant chemotherapy of suspected Wilms tumor rupture: Consequences on therapeutic choices. Issue 6 (17th February 2019) - Le Rouzic, Marie‐Amelyne; Mansuy, Ludovic; Galloy, Marie‐Agnès; Champigneulle, Jacqueline; Bernier, Valérie; Chastagner, Pascal
Abstract: Introduction: According to SIOP criteria, every patient presenting with preoperative Wilms tumor (WT) rupture must receive abdominal radiotherapy. Neoadjuvant chemotherapy reduces tumor volume and is responsible for the development of peritumoral capsule formation, which can mask tumor rupture on histological analysis, while it was clinically or radiologically obvious at diagnosis. Yet, there are no protocol recommendations for this particular presentation. Objectives: Study the agreement between clinicoradiological signs and histological confirmation after neoadjuvant chemotherapy of suspected WT rupture and describe the therapeutic choices arising in consequence. Methods: Descriptive retrospective study on a monocentric series of patients with WT between June 1991 and August 2017. Results: Out of 71 patients, 28 presented with suspected tumor rupture. We observed good agreement between clinical and radiological signs of suspected rupture (κ coefficient: 0.67). However, we assessed poor agreement between these signs and histological conclusions after neoadjuvant chemotherapy (κ coefficient: 0.27). Only five patients with clinicoradiological signs were overtreated with radiotherapy while tumor rupture had been refuted after histological review. The notion of abdominal trauma and the presence of intraperitoneal effusion seemed to guide collegial decision to overtreat these patients. No statistical difference in survival between patients with and without suspicion of tumor rupture at diagnosis was observed. Conclusion: This study highlights the need for recommendations in case of discrepancy between radiological and histological signs of rupture at diagnosis and after neoadjuvant chemotherapy. A study with stronger statistical power is necessary to define criteria that would lead to optimization of treatment in this context.